Pendidikan Islam Dalam Sistem Pendidikan Nasional - Adelia Putri; Putri Wulandari Nasution; Syarah Syarif; Gusmaneli Gusmaneli (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Islamic religious education is education that teaches the values of goodness which then its implementation is applied in life. Islamic education itself has an important role in the history of the development of the Indonesian nation, especially in terms of the historical dimension where Islamic education has been a formal education for centuries known as pesantren. The purpose of this study is to determine the relationship, the role of Islamic education in the national education system because to make a person who is balanced from an intellectual perspective, religious education is needed, namely Islamic education in order to achieve the goals of national education. The method used in this research uses qualitative research methods with the type of library research. Based on the research results, it can be concluded that Islamic education in the national education system is Islamic education occupying a position as a formal, non-formal, informal, and religious institution.